Temporal headache and jaw claudication may be the key for the diagnosis of giant cell arteritis - Peral-Cagigal, Beatriz (Med Oral Patol Oral Cir Bucal, 2018)
BACKGROUND: Temporal artery biopsy (TAB) is a surgical procedure with a low positive yield. The purpose of this study is to determine which variables are the most important in the giant cell arteritis (GCA) diagnosis. The objective of this evaluation is to improve the percentage of positive temporal artery biopsy and if possible, avoid the biopsy in some cases. MATERIAL AND METHODS: A retrospective clinical study consisted of 90 patients who had undergone TAB at the Río Hortega Hospital (Spain) from January 2009 to December 2016. Clinical findings, erythrocyte sedimentation rates (ESR) and other laboratory parameters, American College of Rheumatology (ACR) criteria for GCA score and biopsy results were recorded. RESULTS: Nineteen (21.1%) biopsies were positive for GCA. The mean age in positive TAB was 78.6 years old (SD 7.93), and 73.7% were female. Presence of temporal headache (p = 0.003), jaw claudication (p = 0.001), abnormal artery exploration (p = 0.023), elevated erythrocyte sedimentation rate (p = 0.035), CRP (p = 0.018) and platelets (p = 0.042), were significantly associated with GCA. Multivariate logistic regression revealed that the best predictors for the diagnosis of GCA are headache and jaw claudication, adjusted by sex, age, and temporal exploration. CONCLUSIONS: TAB has benefit only for patients who score a 2 or 3 on the ACR criteria for GCA without biopsy. These findings highlight the need for a better diagnostic strategy for patients with suspected temporal arteritis. Key words:Giant cell arteritis, horton arteritis, vasculitis, temporal artery biopsy, jaw claudication, temporal headache.